STUDI IN VIVO PRODUK SEREAL DARI TEPUNG BEKATUL DAN TEPUNG UBI JALAR SEBAGAI PANGAN FUNGSIONAL - Chandra Utami Wirawati; Dwi Eva Nirmagustina (Jurnal Teknologi & Industri Hasil Pertanian, 2009)
Rice bran has been known to contain bioactive components, namely oryzanol which has some  effects of improving human health, one of these effects is to lower cholesterol content.  The use of rice bran flour as subtitued ingredient on cereal products with 50% rice bran flour, 50% sweet potato flour, 40% tapioca flour, 10% modified starch, 8% sugar, 8% milk powder, 4% cocoa powder, 2,8% salt and 0,5% baking soda composition.  This study was aimed to determine the effect of rice bran flour in cereal product on blood cholesterol levels of rats.  The results showed that cereal product was able to lower LDL cholesterol levels on rat’s blood, each at 57 mg/dl and 10 mg/dl, and increased HDL cholesterol and triglyceride rat’s blood for 24 mg/dl and 107 mg/dl respectively. Keywords: product cereal, rice bran, cholesterol